Kinesthetic illusions induced by muscle tendon vibration: The orientation of the vibration motor as a new methodological factor? - Lydiane Lauzier; Jacques Abboud; François Nougarou; Louis-David Beaulieu (PLoS ONE)
Purpose/aim To investigate the impact of changing the rotational orientation of the vibrating motor on kinesthestic illusions. Materials and methods Twenty healthy individuals received vibration over the wrist flexor muscles of dominant and non-dominant sides (80 Hz, 1 mm, 10 seconds) using four conditions (3 trials/conditions) defined by the rotational direction of the vibrator's eccentric rotating mass according to the anatomical position: (1) proximodistal, (2) distoproximal, (3) mediolateral and (4) lateromedial. Non-parametric statistical analyses were used to compare illusion characteristics across conditions. Results Lateromedial rotation created illusions that were more often in unexpected directions compared to the other rotational orientations. Distoproximal rotation was more likely to evoke kinesthetic illusions of wrist extension (76.8%) compared to lateromedial rotation (57.7%; p = 0.009). The latter led more frequently to complex/combined movement illusions (26.1%) especially with an ulnar deviation component (17.7%) compared to the other rotational directions. Conclusion Results from the present study demonstrated that the rotational orientation can influence illusory perceptions, but not to a great extent. Distoproximal rotation was more effective to elicit the expected illusions of wrist extension, compared to the lateromedial orientation that more often caused complex and variable perceptions of movement. Distoproximal rotation should thus be preferred if clear and reproducible perceptions are required and lateromedial might serve as a way of creating illusions more akin to everyday functional movements. Although the exact underlying mechanisms remain unclear, our work raises awareness on the importance of gaining a better understanding and control over methodological factors that could affect kinesthetic illusions.